Multicultural Counseling to Foster Politeness in Schools: A Systematic Literature Review - Erlindawati Erlindawati; Silvianetri Silvianetri (Jurnal Counseling Care, 2025)
This study explores the role of multicultural counseling in fostering politeness values in schools through a Systematic Literature Review (SLR) guided by PRISMA standards. Schools are not only places of knowledge transfer but also spaces for character development, where politeness defined as respect, etiquette, and social responsibility is central to creating a positive learning climate. A systematic search across Scopus, Google Scholar identified 337 records; after screening and eligibility checks, 14 peer-reviewed articles were included. Findings highlight four dimensions: first, cultural narratives and symbols such as Ghanaian Adinkra and Indigenous healing traditions serve as effective means of internalizing respect; second, counselor multicultural competence reduces bias, prevents microaggressions, and builds inclusive relationships; third, conceptual studies affirm respect, empathy, justice, and courtesy as universal counseling values; and fourth, embedding multicultural perspectives into counselor training and school curricula underscores the institutional role of politeness in education. Overall, multicultural counseling emerges as both a preventive and educational strategy that bridges cultural diversity with universal ethical values. By integrating cultural appreciation and value-based practices, schools can systematically cultivate politeness as a cornerstone of character education, ultimately promoting respect, tolerance, and social harmony in diverse learning environments.